Can Financial Development Contribute to Economic Growth in Asian Countries? - Furuoka, Fumitaka (AEI Insights, 2023)
This paper examines the impact of financial development on economic growth in Asia. In other words, the objective of current paper is to examine the relationship between economic growth and financial development in 10 countries in Asia. It employs systematic time-series econometric methods, namely, the unit root test, the cointegration test, the cointegrating regression analysis, the vector error correction analysis and the Granger causality analysis. The source of data was the “World Development Indicators”. The empirical findings indicated some interesting characteristics in the finance–development nexus in Asia. Interesting findings that financial development could contribute financial development in Singapore only. By contrast, economic growth may induce financial development in China and Pakistan. These findings have some notable policy implications. Singaporean government may need to understand the importance of financial sector in its economy.